a) 26.7×35.8

by

123.6+45

b) 869+123+745

by

9×5

c) 25642−7852

by

0.0258×9551

d) 3258.23

by

1869+55

by

123.6+45

b) 869+123+745

by

9×5

c) 25642−7852

by

0.0258×9551

a) 26.7×35.8

by

123.6+45

b) 869+123+745

by

9×5

c) 25642−7852

by

0.0258×9551

d) 3258.23

by

1869+55

You must be logged in to post a comment.

Step-by-step explanation:Answer

Open in answr app￼

The given sets are:

A={1,2,4,5}, B={2,3,5,6}, C={4,5,6,7}

∴ B∪C={2,3,4,5,6,7}

A−(B∪C)={1}

A−B={1,4}

A−C={1,2}

(A−B)∩(A−C)={1}

we have to verify, A−(B∪C)=(A−B)∩(A−C)

LHS=A−(A∪C)

={1}

RHS=(A−B)∩(A−C)

={1}

Hence, A−(B∪C)=(A−B)∩(A−C)